A parameter study of solid oxide electrolysis cell degradation: Microstructural changes of the fuel electrode. (20th June 2018) - Hoerlein, Michael Philipp; Riegraf, Matthias; Costa, Rémi; Schiller, Günter; Friedrich, K. Andreas
Abstract: A parameter study of 20 solid oxide electrolysis cells was carried out to systematically investigate long-term degradation each over 1000 h under variation of temperature, humidity and current density. The influence of operating temperature was investigated between 750 and 850 °C, the humidity ranged from 40% to 80% H2 O, and the current density varied between open circuit voltage (OCV) and 1.5 A cm −2 . The progress of degradation was monitored in-situ by electrochemical impedance spectroscopy. Five different contributions to the spectra were identified by calculating the distribution of relaxation times and separated via a complex non-linear square fitting routine. The present work focuses on the degradation of the fuel electrode. From SEM analysis, Ni depletion and an increased pore fraction close to the electrode/electrolyte interface was derived, which is correlated with an increased ohmic resistance of the cells. This unidirectional transport of Ni away from the fuel electrode/electrolyte interface leads to an effective electrolyte extension and is the main source of degradation. Ni depletion is shown to be driven by current density and its extent is shown to be dependent on the complex interplay between the operating parameters current density, anode overpotential, humidity and temperature. It is particularly pronounced for p H2 O larger than 0.8 atm and temperatures above 800 °C. Furthermore, the fuel electrode electrochemistry also exhibits degradation in the high-frequency region around 10 4  Hz.